Comparison of the Effects of Attachment and Relaxation Instruction on the Third Trimester Depression and Post-partum Blues - Akbarzade, Marzieh; Rafiee, Bahare; Asadi, Nasrin; Nematollahi, Azar; Taheri, Mina (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: This study was conducted to compare the effects of attachment and relaxation instruction on the third trimester depression and post-partum blues. Methods: Randomized controlled trial in three arms (teaching relaxation, maternal-fetal attachment skills and control) of 42 women each among 126 nulliparous women in a selected educational center (Hafez) affiliated to Shiraz University of Medical Sciences, Shiraz, Iran from January 2012 to February 2012. The patients filled out the demographic data sheet, Cranley maternal-fetal attachment test questionnaire, Beck depression questionnaire, Spilberger anxiety and written consent Questionnaires. Results: The mean and standard deviation of the Beck depression test scores after the intervention were 20.5±3/10, 21.1±3.8, and 23.2±3.8 for the attachment, relaxation, and control group, respectively. The changes were statistically significant according to the one-way ANOVA test (P= 0.002). The post-hoc test was statistically significant for the decrease in the depression groups after delivery in the attachment (P = 0.01) and relaxation group (P = 0.01).The reduction in the depression scores before, and after the intervention in the attachment (P=0.001) and relaxation group (P = 0.002) was significant based on paired-t-test results. However, the control group showed an increase in the depression scores which were statistically significant (P= 0.04). Conclusions: Prenatal educational program based on attachment and relaxation training can improve maternal identity role and reduce maternal depression. This study showed that preventing post-partum depression by simple, available and cost beneficial training programs skills.